Frekuensi Pemberian Pakan Buatan Berbasis Limbah Untuk Produksi Kepiting Bakau Cangkang Lunak - Aslamyah, Siiti; Fujaya, Yushinta (Hasanuddin University, 2014)
Feed eficiency is largely determined by its availability in suficient quantities and on timefeeding, s o it is necessary to study the frequency of feeding for the best production of soft shell crab. Four feeding frequency (1 time per day, 1 time per 2 days, 1 time per 3 days, and 1 time per 4 days) tested in this study. Feed with nutrient composition of 30.86% protein, 7.2% fat, nitrogen free extract (NFE) 48.89%, crude fiber 5.7% enriched with vitomolt 0.1041 5 mg/g of feed to the standard dose and 0.4166 mg vitomolt/g feed to high doses; or equal to 700 ng vitomolt/g crab. Test crabsof Scylla sp. reared in crabs box and placed in the pond. The results showed the frequency of feeding 1 time per 2 days resulted in the highest percentage of molting (66.67%) and the lowest percentage of moulting was found at 1 per 4 times a day of feeding (36.67%). Growth param eters such as weight and carapace width, and feed eficiency did not difer among all treatments. Thus, feeding in the soft shell crab for the maximum production can be done with a frequency of 1 time per 2 days .